Optimization of petroleum crude oil treatment using hydrogen sulfide scavenger - H.A. Elmawgoud; T.M. Elshiekh; M. Abdelkreem; S.A. Khalil; A.M. Alsabagh (Egyptian Journal of Petroleum)
Hydrogen sulfide scavenging is one of the preferred methods for minimizing the operational risks and corrosion in crude oil production facilities. This paper deals with the determination of the optimum values of retention times of scavenging hydrogen sulfide from the crude oil produced at different conditions in one of the Egyptian petroleum companies using EPRI H2S scavenger solution (one of the chemical products of Egyptian Petroleum Research Institute). The retention time depends on several operating condition variables such as injection dose rate, pipe length, pipe diameter, crude oil velocity, pressure and inlet H2S concentration. The hydrogen sulfide scavenger injected into the crude oil pipeline must be contacted with the crude oil for a suitable a specified time (retention time) to reduce the concentration of H2S to the desired value which is usually less than 10 ppmv. The optimization results were obtained using the software program LINGO. It was found that the optimum values of H2S scavenger retention time of the scavenging of hydrogen sulfide are increased by increasing the pipe diameter and the inlet H2S concentration, while decreased by increasing the pipe length, gas molar mass velocity, injection dose rate, crude oil velocity and pressure. Keywords: Crude oil optimization, Retention time, Hydrogen sulfide removal